Association between Interleukin-1 Gene Single Nucleotide Polymorphisms and Ischemic Stroke Classified by TOAST Criteria in the Han Population of Northern China. (25th August 2013) - Zhang, Zheng; Liu, Li-Jun; Zhang, Chen; Yu, Yong-Peng
Abstract : Increasing evidence suggests that IL-1 β (C-511T) and IL-1 α (C-889T) genes polymorphisms are associated with the susceptibility to cardiocerebral vascular disease. In this paper, we investigated the relationships between these polymorphisms and the risk of ischemic stroke (IS) classified by TOAST criteria in the north Chinese Han population. 440 cases of IS and 486 age- and gender-matched controls of Chinese Han population were enrolled. Association study showed that the TT genotype and T allele of IL-1 α -889 C/T were significantly associated with IS of a large artery atherosclerosis (LAA) (TT: OR = 2.01, 95% CI = 1.34–3.0, and P < 0.001 ; T: OR = 1.44, 95% CI = 1.18–1.78, and P = 0.001 ). However, there was no significant difference in the distribution of IL-1 α -889 C/T genotypes and allele frequencies between the two subgroups (small-artery occlusion (SVD) and cardioembolism (CE)) of IS and control groups. No significant association was also found between the IL-1 β -511 TT genotype and T allele (TT: OR = 0.79, 95% CI = 0.56–1.11, and P = 0.175 ; T: OR = 0.83, 95% CI = 0.68–1.01, and P = 0.066 ) and IS as well as subgroups of CE and SVD. Our results implicated that IL-1 α -889 C/T gene polymorphism might be associated with the susceptibility to IS, especially to IS with LAA, in a north Chinese Han population.